Pelatihan Manajemen Mutu Pelayanan Keperawatan sebagai Upaya Peningkatan Kepuasan Pasien di Rumah Sakit - Solehudin Solehudin; Inas Syabanasyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Quality nursing services are an essential indicator of hospital performance because they directly influence patient satisfaction. Nurses, as healthcare professionals who interact most frequently with patients, play a strategic role in ensuring high-quality healthcare services. However, challenges remain in implementing nursing quality management, including inconsistent application of service standards, ineffective therapeutic communication, and limited understanding of nursing quality indicators. This community service program aimed to improve nurses’ knowledge and competencies regarding nursing service quality management to enhance patient satisfaction in hospitals. The program was conducted through training sessions, interactive lectures, case discussions, nursing service simulations, and evaluations using pre-tests and post-tests. A total of 35 nurses from inpatient wards and other service units participated in the activity. Evaluation was carried out to assess participants’ knowledge improvement after the training. The results demonstrated an increase in participants’ average knowledge scores from 68.4 during the pre-test to 87.6 during the post-test. Participants showed improved understanding of quality management concepts, nursing quality indicators, SERVQUAL dimensions, patient safety principles, and strategies for improving patient satisfaction. The activity also enhanced participants’ awareness of the importance of a quality culture in nursing services. In conclusion, nursing service quality management training effectively improves nurses’ knowledge and understanding of quality improvement efforts and patient satisfaction enhancement. Continuous training programs are recommended to support the development of a quality culture in hospitals